"Wherever You Go, You Will Be a Polis": Spatial Practices and Political Education in Computer-Supported Collaborative Learning Discussions. Issue 2 (3rd April 2017) - Slakmon, Benzi; Schwarz, Baruch B.
Abstract : The aim of this article is to increase understanding of the development of spatial practices in virtual learning environments. The spatial change and development in 38 small-group e-discussions taken from a data set of a yearlong 8th-grade humanities course are described and analyzed. We show that the focus on spatial changes in computer-supported collaborative learning (CSCL) environments enriches the scope of activities in virtual environments that are usually studied from the perspective of productivity and disciplinary knowledge building only. We argue that tracing spatial changes enables researchers to scrutinize the freedom to act and exercise power over others, something crucial for the development of political agency. We show that these developments are decisive for students to become competent citizens. Implications the study has for CSCL design and for political education are discussed.